Pengujian Tarik Plat Baja Karbon Rendah Setelah Proses Pemanasan Dengan Suhu 800oC Di Quenching Biosolar - Ahmadin ahmadin (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Low carbon steel plates are widely used in construction fields such as car bodies, runway plates, trellises and others where high resistance and tenacity are required. This process is carried out at 800oC for 30 minutes then in biosolar quenching. The results of the average non-settlement tensile stress obtained yield stress ?y = 13.02 kgf / mm2, ultimate stress ?u = 21.58 kgf / mm2, breaking voltage ?f = 18.66 kgf / mm2. The results of the average air tensile stress obtained yield stress ?y = 9.53 kgf / mm2, ultimate stress ?u = 18.94 kgf / mm2, breaking voltage ?f = 12.39 kgf / mm2. The results of the average air tensile stress obtained yield stress ?y = 18.16 kgf / mm2, ultimate stress ?u = 26.23 kgf / mm2, breaking voltage ?f = 22.05 kgf / mm2. The results of the average biosolar tensile stress obtained yield stress ?y = 18.98 kgf / mm2, ultimate stress ?u = 28.12 kgf / mm2, breaking voltage ?f = 24.65 kgf / mm2. From the above data biosolar cooling media will be proposed to increase. From this study it was concluded that biosolar is the best as a cooling medium that can increase tensile material compared to air conditioning media.